Comparative clinical profile of mirtazapine and duloxetine in practical clinical settings in Japan: a 4-week open-label, parallel-group study of major depressive disorder - Nagao K (Dove Medical Press, 2013)
Kei Nagao,1,2 Taro Kishi,1 Masatsugu Moriwaki,1 Kiyoshi Fujita,3,4 Shigeki Hirano,5 Yoshio Yamanouchi,1 Toshihiko Funahashi,2 Nakao Iwata1 1Department of Psychiatry, Fujita Health University School of Medicine, Toyoake, Aichi, Japan; 2Department of Psychiatry, The Jindai Hospital, Toyota, Aichi, Japan; 3Department of Psychiatry, The Okehazama Hospital, Toyoake, Aichi, Japan; 4The Neuroscience Research Center, Toyoake, Aichi, Japan; 5Department of Psychiatry, The Toyota Memorial Hospital, Toyota, Aichi, Japan Abstract: No studies have compared mirtazapine with duloxetine in patients with major depressive disorder (MDD). Fifty-six patients were nonrandomly assigned to a 4-week treatment with either 15 to 45 mg/day of mirtazapine (n = 22) or 20 to 60 mg/day of duloxetine (n = 34). The primary efficacy measurements were the Hamilton Rating Scale for Depression (HRSD) and the Montgomery–Åsberg Depression 6-point Rating Scale (MADRS) scores. The second efficacy measurements were the response and remission rates of treatment. Tolerability assessments were also performed. Fifty-six patients (43 male; age, 43.6 years) were recruited. There was no significant difference in the discontinuation rate between the mirtazapine and duloxetine treatment groups (P = 0.867). Both mirtazapine and duloxetine significantly improved the HRSD and MADRS scores from baseline (P < 0.0001–0.0004). While mirtazapine was superior to duloxetine in the reduction of HRSD scores (P = 0.0421), there was no significant change in MADRS scores in terms of between-group differences (P = 0.171). While more somnolence was observed with mirtazapine (P = 0.0399), more nausea was associated with duloxetine (P = 0.0089). No serious adverse events were observed for either antidepressant. Mirtazapine and duloxetine were safe and well-tolerated treatments for Japanese patients with MDD. Double-blind controlled studies are needed to further explore the efficacy and safety of mirtazapine and duloxetine in Japanese patients with MDD. Keywords: mirtazapine, duloxetine, major depressive disorder